Effectiveness of Bdellovibrio Against the Immune System of White Shrimp (Litopenaues vannamei) Infeksion with Vibrio harveyi Bacteria - I Wayan Rainbow; Azhar, Fariq; Scabra, Andre Rachmat (Jurnal Media Akuakultur Indonesia, 2025)
White shrimp (Litopenaeus vannamei) is an aquatic biota that is included in the leading commodity of aquaculture. The Vibrio harveyi bacteria can cause up to 80% death in white shrimp. The predatory Bdellovibrio is highly regarded as an alternative source of antibiotics and has been reported to have the potential to control shrimp pathogens such as Vibrio chalerae and Vibrio parahaemolyticus. The aim of this study was to analyze the effect of giving Bdellovibrio on the immune system of vaname shrimp infected with Vibrio harveyi bacteria. This research is experimental using a completely randomized design (CRD), which consists of 5 treatments and 3 replications. This study was experimental using a completely randomized design (CRD), which consisted of 5 treatments and 3 replications. Treatments in the study included P1 (+)(Not given Bdellovibrio and tested with Vibrio harveyi), P2 (-) (Not given Bdellovibrio and tested with NaCL), P3 (Given 30 ppm Bdellovibrio and tested with Vibrio harveyi), P4 (Given Bdellovibrio 50 ppm and tested with Vibrio harveyi), and P5 (Given Bdellovibrio 70 ppm and tested with Vibrio harveyi). In this study, the best treatment value was obtained, namely P5 treatment, the THC value was 16.94 x 106 cells/ml, the DHC value in hyaline cells was 59.33%, the granular cells were 24%, the semi-granular cells were 16.67%, the AF value 64.82%, TBC value 5.98 x 108 CFU/ml, TVC value 1.43 x 107 CFU/ml, FCR value 1.23, specific length growth rate 19.4%/day, specific weight growth rate 9 .96%/day, the absolute length value is 8.73 cm, the absolute weight is 61 grams and the SR value is 77.78%. From this research, it was concluded that administration of Bdellovibrio in the rearing media at different doses was able to improve the immune system and survival of White shrimp tested with Vibrio harveyi bacteria